From Centralization to Citizen Empowerment: Advancing Environmental Democracy in Fiji - Gultom, Yosua Saut Marulitua (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2025)
This study examines Fiji’s intricate governance landscape, a product of its colonial past, military interventions, and subsequent constitutional reforms, which have collectively fostered a highly centralized political system. By critically analyzing the evolution of Fiji’s political structures alongside the case study of FIJI Water, the research highlights significant tensions between national unity efforts and the preservation of traditional indigenous governance. The study employs qualitative methodologies, drawing on extensive secondary data from academic literature, government documents, and media reports to assess the implications of centralized authority on democratic participation and environmental policy. Findings reveal that while recent reforms have sought to eliminate ethnic-based representation and promote a unified national identity, they have also marginalized traditional institutions and limited public accountability. In parallel, the FIJI Water controversy illustrates the broader conflict between corporate interests and the sustainable management of natural resources, as local communities continue to face challenges in accessing clean water despite the country’s global brand image. The analysis underscores the urgent need for legal reforms—such as enforcing Free, Prior, and Informed Consent (FPIC) and decentralizing governance structures—to empower indigenous groups and strengthen public participation in environmental decision-making. Ultimately, the study argues that a recalibrated governance model, which integrates environmental democracy with political reforms, is essential for ensuring sustainable development and upholding human rights in Fiji.